Influence of diabetes mellitus on osseointegration: A narrative review (Research, Society and Development, 2024)
Diabetes mellitus is a chronic disease affecting millions of people worldwide and can significantly impact osseointegration, the process by which an implant integrates with the bone. This narrative review explores how Diabetes mellitus influences osseointegration by analyzing various studies and clinical evidence. Patients with Diabetes mellitus often experience difficulties in bone healing and a higher risk of implant failure due to metabolic alterations and chronic inflammation. Additionally, hyperglycemia can interfere with the formation of new blood vessels, crucial for bone integration. The review also discusses potential strategies to improve osseointegration in diabetic patients, including strict glucose level control and the use of advanced biomaterials. The aim of this narrative review is to provide a comprehensive overview of the challenges and solutions in osseointegration for patients with Diabetes mellitus.